2012
DOI: 10.1093/ndt/gfs335
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fgf23 and  klotho in developing embryonic tissues and adult kidney of the zebrafish, Danio rerio

Abstract: Fibroblast growth factor 23 (FGF23) is an endocrine hormone that is secreted by bone and acts on the kidney and parathyroid glands to regulate phosphate homeostasis. The effects of FGF23 on phosphate homeostasis are mediated by binding to FGF receptors and their coreceptor, αklotho, which are abundantly expressed in the kidney and parathyroid glands. However, the mechanisms of how FGF23 regulates phosphate handling in the proximal tubule are unclear because αklotho is primarily expressed in the distal nephron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In continued research, mainly driven by Faul and coworkers ( 21 , 56 , 59 61 ), several experimental settings were used to determine whether the FGF23 association with LVH was causative or purely associative. The authors concluded that FGF23 is within the causal pathway of CKD-associated LVH development.…”
Section: Specific Focus Upon Fgf23 As the Driving Force For Lvhmentioning
confidence: 99%
“…In continued research, mainly driven by Faul and coworkers ( 21 , 56 , 59 61 ), several experimental settings were used to determine whether the FGF23 association with LVH was causative or purely associative. The authors concluded that FGF23 is within the causal pathway of CKD-associated LVH development.…”
Section: Specific Focus Upon Fgf23 As the Driving Force For Lvhmentioning
confidence: 99%
“…Furthermore, FGF23 might play important roles during embryonic development. In zebrafish embryos, FGF23 expression is confined to the cells of the corpuscles of Stannius which regulate mineral ion homeostasis in advanced bony fish, also called teleosts ( 295 ). During embryonic mouse development, FGF23 is predominantly expressed in somites, heart, and liver ( 296 ).…”
Section: Discussionmentioning
confidence: 99%
“…50 FGF9 and FGF20 play an important role in nephrogenesis, 50,51 whereas FGF23 expression was not found in the developing zebrafish kidney. 52 FGF23 belongs to the family of fibroblast growth factors, in which the majority of proteins regulate embryogenesis, growth, and angiogenesis and play an important role in organ regeneration and repair. 53 Whether kidney-derived FGF23 has an autocrine or paracrine function in the renal repair system merits further study.…”
Section: Discussionmentioning
confidence: 99%